The Subject(s) of Human Rights Crises, Violations, and Asian/American Critique - Schlund-Vials, Cathy; Beauregard, Guy; Lee, Hsiu-chuan (Temple University Press, 2019)
The field of Asian American studies grew out of mid-twentieth century civil rights struggles, anti-war protests, and third world liberation movements. As a result, human rights issues have always been part of Asian American studies, though they've been largely peripheral to the interdiscipline. This edited collection bring Asian American studies to the center of human rights critique by engaging with "the possibilities and the limits of the stories that have circulated and the knowledge that has been produced around the broad topic of 'human rights' understood primarily as a post-1945 discourse that has profoundly affected the movements of people and relations of power across the Pacific." The collection brings together scholars from North America and Asia in order to approach the issue of human rights from both sides of the Pacific.